Post-periapsis pancakes: sustenance for self-gravity in tidal disruption events. Issue 4 (1st December 2015) - Coughlin, Eric R.; Nixon, Chris; Begelman, Mitchell C.; Armitage, Philip J.; Price, Daniel J.
Abstract: A tidal disruption event, which occurs when a star is destroyed by the gravitational field of a supermassive black hole, produces a stream of debris, the evolution of which ultimately determines the observational properties of the event. Here, we show that a post-periapsis caustic – a location where the locus of gas parcels comprising the stream would collapse into a two-dimensional surface if they evolved solely in the gravitational field of the hole – occurs when the pericentre distance of the star is of the order of the tidal radius of the hole. It is demonstrated that this 'pancake' induces significant density perturbations in the debris stream, and, for stiffer equations of state (adiabatic index γ ≳ 5/3), these fluctuations are sufficient to gravitationally destabilize the stream, resulting in its fragmentation into bound clumps. The results of our findings are discussed in the context of the observational properties of tidal disruption events.